Effect of Aspergillus oryzae on the rumen fermentation of Pennisetum purpureum cv. Cuba CT-115 through the in vitro gas production technique - Sosa, Areadne; Galindo, Juana; Bocourt, Ram?n; Rodr?guez, R.; Albelo, Nereida; Oramas, A. (Cuban Journal of Agricultural Science, 2010)
In order to determine the effect of Aspergillus oryzae on the rumen fermentation of Pennisetum purpureum cv Cuba CT-115, an experiment was conducted with two trials, according to complete random design using the in vitro gas production technique. Five treatments were assessed. The doses of 0, 0.5, and 1 mL of A. oryzae culture in 80 mL of incubation solution were compared in the first stage, and those of 0, 0.1, and 0.2 mL culture in 80 mL of incubation solution were compared in the second. Four repetitions were carried out per treatment. In the first trial, the readings were performed every 3 h up to 24 h of incubation and, in the second, every two hours up to 77 h. The parameters of the fermentation kinetics were determined in the doses of 0, 0.1, and 0.2 mL. The outcomes showed that the adequate dose of microbial additive was of 0.2 mL of culture in 80 mL of incubation solution. The values of gas production attained with this level of inclusion were higher (P < 0.001) than those of the control without inoculum. This dose showed higher potential of gas production, higher fermentation speed, and lower lag phase, compared with the control without inoculum. The levels of 0.5 and 1 mL of A. oryzae culture provoked a decline in gas production. It is suggested that the addition of this strain of A. oryzae at doses of 0.2 mL of culture in 80 mL of incubation solution is able of stimulating the rumen fermentation of Pennisetum purpureum in experiments under in vitro conditions. Key words: microbial additives, Aspergillus oryzae, gas production, roughages.